1975
DOI: 10.1128/aac.8.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Protein Synthesis in Intact HeLa Cells

Abstract: Polysome analysis has proved to be a sensitive probe for the mode of action of inhibitors of protein synthesis in intact HeLa cells. To classify the active compounds as inhibitors of initiation, elongation, or termination, their effects on the cellular polyribosome pattern were compared under three conditions. These conditions tested (i) their direct effect on the polyribosome profile; (ii) their effect on ribosome run-off produced by hypertonicity; and (iii) their effects on recovery from hypertonicity. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 35 publications
2
31
0
Order By: Relevance
“…Pactamycin and harringtonine, the other drugs that were tested, are both protein synthesis inhibitors that lead to depletion of polysomes in eukaryotic cells (Kappen et al 1973;Tscherne and Pestka 1975;Fresno et al 1977). As with puromycin, we found that both reduced the BiFC signal in extracts (Fig.…”
Section: The Bifc Interaction Between Rps18 and Rpl11 Occurs In The 8mentioning
confidence: 63%
See 1 more Smart Citation
“…Pactamycin and harringtonine, the other drugs that were tested, are both protein synthesis inhibitors that lead to depletion of polysomes in eukaryotic cells (Kappen et al 1973;Tscherne and Pestka 1975;Fresno et al 1977). As with puromycin, we found that both reduced the BiFC signal in extracts (Fig.…”
Section: The Bifc Interaction Between Rps18 and Rpl11 Occurs In The 8mentioning
confidence: 63%
“…To assess more directly the dependence of the BiFC signal on translation, we first compared the effects of emetine and puromycin. These translation inhibitor drugs have different mechanisms of action (Tscherne and Pestka 1975): Emetine blocks ribosomal polypeptide elongation, freezes 80S, and stabilizes polysomes (Grollman 1968), whereas puromycin is an aminoacyl-tRNA-like molecule that causes premature translation termination by serving as acceptor for the peptidyl-tRNA and leads to rapid breakdown of polysomes (Nathans and Lipmann 1961). As exemplified in Supplemental Figure S3D, puromycin causes dissociation of the two subunits at least in vitro (Blobel and Sabatini 1971).…”
Section: The Bifc Interaction Between Rps18 and Rpl11 Occurs In The 8mentioning
confidence: 99%
“…1C, FIG 2 CBF␤ does not affect translational activity on Vif mRNA. Polysome analysis was done using a modification of a previously described protocol (63). Briefly, HeLa-KD cells (9 ϫ 10 6 in a 75-cm 2 flask) were transfected with 12 g of pcDNA-hVif together with either 3 g of pcDNA-CBF␤ or 3 g of empty vector DNA.…”
Section: Resultsmentioning
confidence: 99%
“…3B). The Golgi morphology of compound-treated cells also differed from the characteristic Golgi architecture of cells treated with anisomycin, a peptidyl transferase inhibitor shown to induce apoptosis in HeLa cells (57). Other small-molecule compounds known to affect Golgi morphology include nocodazole (10), a microtubule-disrupting agent, and BFA, a known trafficking inhibitor that causes complete dispersal of the Golgi apparatus (24,42).…”
Section: Vol 75 2007 Small-molecule Inhibitors Of Toxin Transport 4555mentioning
confidence: 99%